Double-layer pre-composite type polymer pre-paved waterproof roll material and preparation method thereof

CN122976158APending Publication Date: 2026-10-27HEBEI LANFU WATERPROOF MATERIAL CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611303942.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-26
Publication Date
2026-10-27

AI Technical Summary

Benefits of technology

(1)本发明通过第一无纺布、第一防水层、第二无纺布、第二防水层、涂胶层和涂砂层组成双层预复合型高分子预铺防水卷材,并在防水层中加入混合稀土,提高了防水卷材的拉伸强度、延伸率和耐腐蚀性,增强材料的抗老化性、耐高温、抗低温、增强不透水性,可以更好的适应建筑结构主体形变,应用场景更加广泛。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure REF-OBJ-1786503069124-000002
    Figure REF-OBJ-1786503069124-000002
  • Figure REF-OBJ-1786503069124-000003
    Figure REF-OBJ-1786503069124-000003
  • Figure REF-OBJ-1786503069124-000004
    Figure REF-OBJ-1786503069124-000004
Patent Text Reader

Abstract

The application discloses a double-layer pre-composite type high polymer pre-paving waterproof roll applied to the field of building waterproof technology and a preparation method thereof. The double-layer pre-composite type high polymer pre-paving waterproof roll is composed of a first non-woven fabric, a first waterproof layer, a second non-woven fabric, a second waterproof layer, a glue coating layer and a sand coating layer, and mixed rare earth is added to the waterproof layer, so that the tensile strength, the elongation rate and the corrosion resistance of the waterproof roll are improved, the aging resistance, the high-temperature resistance, the low-temperature resistance and the impermeability of the reinforcing material are enhanced, the waterproof roll can better adapt to the deformation of a building structure main body, and the application scene is more extensive.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of building waterproofing technology, and in particular to a double-layer pre-composite polymer pre-laid waterproof membrane and its preparation method. Background Technology

[0002] In the field of construction engineering, waterproofing has always been a crucial aspect. Building waterproofing primarily prevents rainwater, groundwater, and domestic wastewater from seeping into the interior of a building. It protects the main structure, such as concrete and steel reinforcement, from water erosion and aging, extending the building's lifespan. It also prevents indoor water seepage from causing damage to interior decorations, short circuits in electrical appliances due to moisture, and prevents mold growth that can harm human health. Furthermore, it reduces the cost of frequent leak repairs and ensures that all spaces in the house are dry, safe, and usable normally. However, traditional waterproofing materials have gradually revealed many limitations over long-term use.

[0003] In complex environments, especially in key projects with high requirements for durability and corrosion resistance, single-material waterproof membranes often cannot effectively cope with the stress caused by structural deformation, which can easily lead to cracking and failure of the waterproof layer. In order to improve the durability and corrosion resistance of waterproof membranes, adding rare earth elements is currently an advanced way to improve the durability and corrosion resistance of waterproof membranes. For example, Chinese patent application CN117924956A discloses a preparation process of weather-resistant modified bitumen waterproof membrane with added rare earth elements. Rare earth can be used as a catalytic component to improve the polymerization efficiency of ethylene and regulate the molecular structure of polyethylene. It can also be used as a functional additive to modify polyethylene and improve the aging resistance, mechanical properties, flame retardancy or light-shielding properties of the waterproof membrane. Summary of the Invention

[0004] The core of this invention lies in solving the problems of low mechanical strength and poor corrosion resistance of existing waterproof membranes by adding mixed rare earth elements to the waterproof membrane.

[0005] To solve the above problems, the present invention adopts the following technical solution.

[0006] The double-layer pre-composite polymer pre-laid waterproof membrane comprises, from bottom to top, a first non-woven fabric, a first waterproof layer, a second non-woven fabric, a second waterproof layer, an adhesive layer, and a sand coating layer. One edge of the first waterproof layer has an overlapping adhesive layer. The first and second waterproof layers each independently comprise the following raw materials in parts by weight: 50-60 parts polyethylene, 30-40 parts thermoplastic polyolefin, 10-15 parts polyaryletherketone, 15-20 parts filler, 1-2 parts antioxidant, 2-3 parts compatibilizer, and 0.15-0.18 parts mixed rare earth elements. Both the adhesive coating and the overlap adhesive layer are one or more of hot melt adhesive and butyl adhesive; The sand coating layer includes one or more of the following: alumina ceramics, sintered kaolin ceramsite, sintered quartz sand, and sintered refractory clay aggregate.

[0007] Furthermore, the polyaryletherketone is composed of a first polyaryletherketone and a second polyaryletherketone, with different melt indices. The melt index of the first polyaryletherketone is 55 g / 10 min, and the melt index of the second polyaryletherketone is 9 g / 10 min. The mass ratio of the first polyaryletherketone to the second polyaryletherketone is 1 to 3:5.

[0008] Furthermore, both the first and second nonwoven fabrics are high-strength polypropylene nonwoven fabrics, and the cutting width of the first nonwoven fabric is reduced by 10cm compared to the cutting width of the first waterproof layer.

[0009] Furthermore, the filler includes one or more of light calcium carbonate, kaolin, and talc, and the compatibilizer is maleic anhydride-grafted polyethylene.

[0010] Furthermore, the mixed rare earth elements are as follows by the following oxide mass ratios: lanthanum oxide 10–14%, cerium oxide 13–17%, praseodymium oxide 7–11%, neodymium oxide 6–10%, holmium oxide 3–7%, erbium oxide 3–7%, ytterbium oxide 6–10%, scandium oxide 1–3%, samarium oxide 8–12%, yttrium oxide 10–14%, and gadolinium oxide 12–16%.

[0011] The preparation method of double-layer pre-composite polymer pre-laid waterproof membrane includes the following steps: S1. The raw materials of the first waterproof layer and the second waterproof layer are mixed separately, and then extruded and molded to obtain the first waterproof layer sheet and the second waterproof layer sheet; S2. The layers are stacked in the order of first non-woven fabric, first waterproof layer, second non-woven fabric, and second waterproof layer from bottom to top. A 10cm section to be coated with adhesive is reserved at one edge of the first non-woven fabric. After hot pressing, a double-layer composite polymer waterproof membrane is obtained. S3. Apply hot melt adhesive to the second waterproof layer of the double-layer composite polymer waterproof membrane to form an adhesive layer. Then, cover the other end of the edge of the second waterproof layer (in the opposite direction to the reserved end of the first non-woven fabric edge) with a 10cm wide edge film. S4. The composite polymer waterproof membrane with the adhesive layer and edge film is fed into the sand planting equipment to form a sand coating layer on the outer surface of the adhesive layer. After cooling, a double-layer pre-composite polymer pre-laid waterproof membrane is obtained. S5. Apply hot melt adhesive to the edge of the first waterproof layer of the double-layer pre-composite polymer pre-laid waterproof membrane to form an overlapping edge adhesive layer, and then cover with edge film.

[0012] Furthermore, the sand planting equipment includes a conveyor belt machine tool for conveying the movement of double-layer composite polymer waterproof membrane and a sand bucket for uniformly dropping sand. The sand bucket is fixed above the starting end of the conveyor belt machine tool. Electric slide rails are fixedly connected to both the left and right ends of the conveyor belt machine tool. Sliding brackets with the same direction of transmission movement as the conveyor belt machine tool are fixedly connected to the movable ends of the two electric slide rails. Compacting rollers and leveling rollers are rotatably connected between the top and bottom of the two sliding brackets, respectively. Compacting rollers are used for double-layer composite polymer waterproof membranes transported above the roller pressing conveyor belt machine, while leveling rollers are used for double-layer composite polymer waterproof membranes transported below the roller pressing conveyor belt machine. At the other end of the conveyor belt machine tool, a sand receiving box is placed at the bottom. A fine sand pipe is fixedly connected to the top of the sand receiving box. A peeling plate is fixedly connected to the top of the fine sand pipe away from the sand hopper. The top of the peeling plate slides in contact with the double-layer composite polymer waterproof membrane being transported below the conveyor belt machine tool.

[0013] Furthermore, rolling rulers are fixedly connected to the top and bottom edges of both ends of the conveyor belt machine tool, and rolling gears are fixedly connected to both ends of the compaction roller and the leveling roller, with the rolling rulers meshing with the rolling gears.

[0014] Furthermore, the sand receiving box is divided into a coarse sand receiving area and a fine sand receiving area. The coarse sand receiving area is located at the end of the conveyor belt machine tool away from the sand hopper. The coarse sand receiving area and the fine sand receiving area are symmetrically distributed about the fine sand pipe. The top of the fine sand pipe is provided with a sand outlet at the end near the fine sand receiving area. A sand shaking diaphragm is fixedly connected to the outside of the sand outlet. Both ends of the bottom of the fine sand pipe are fixedly connected to a high-speed electric slide table. The end of the sand shaking diaphragm away from the sand outlet is fixedly connected to the movable end of the high-speed electric slide table.

[0015] Furthermore, the fine sand pipe is internally connected to a rotating shaft, and spiral pusher blades and sand pusher plates are sequentially and alternately fixed to the outside of the rotating shaft. The sand pusher plates are arranged parallel to the axial direction of the rotating shaft, and the edges of the sand pusher plates slide in contact with the inner wall of the fine sand pipe. Both ends of the fine sand pipe are fixedly connected to fine sand hoppers, and multiple spiral pusher blades are symmetrically arranged about the middle of the rotating shaft.

[0016] Compared with the prior art, the advantages of this invention are: (1) The present invention consists of a first non-woven fabric, a first waterproof layer, a second non-woven fabric, a second waterproof layer, an adhesive layer and a sand coating layer to form a double-layer pre-composite polymer pre-laid waterproof membrane. Mixed rare earth is added to the waterproof layer to improve the tensile strength, elongation and corrosion resistance of the waterproof membrane, enhance the material’s anti-aging, high temperature resistance, low temperature resistance and impermeability, and can better adapt to the deformation of the main building structure and has a wider range of application scenarios.

[0017] (2) In this invention, coarse sand falling from the sand hopper is spread evenly on the surface of the adhesive layer, and the compaction roller compacts the coarse sand layer spread on the double-layer composite polymer waterproof membrane, so that the gravel at the bottom of the coarse sand layer is fully embedded in the adhesive layer, which effectively improves the bonding effect between the sand coating layer and the adhesive layer. (3) The present invention uses a high-speed electric slide to drive the sand-shaking film to repeatedly retract and expand, so that the fine sand on the sand-shaking film is thrown upward, so that the fine sand comes into contact with and adheres to the coating layer, and the fine sand fills the gap between the coarse sand, effectively reducing the exposed area of ​​the coating layer. In the subsequent contact with the leveling roller, the possibility of the coating layer sticking to the leveling roller is effectively reduced, and the smoothness of the sand surface of the coating layer is effectively improved. Attached Figure Description

[0018] Figure 1 This is a flowchart of the steps of the present invention; Figure 2 This is a three-dimensional structural diagram of the sand planting equipment of the present invention; Figure 3 This is a bottom-view perspective view of the leveling roller of the present invention. Figure 4 This is a three-dimensional structural diagram of the compaction roller and the leveling roller of the present invention; Figure 5 This is a side sectional view of the conveyor belt machine tool of the present invention; Figure 6 This is a demonstration diagram showing the bonding of the compaction roller with the adhesive layer, where the compaction roller applies pressure to the gravel. Figure 7 This is a demonstration diagram showing the falling of gravel that is not in contact with the adhesive layer according to the present invention; Figure 8 This is a demonstration diagram showing the smoothness of the sand surface of the sand coating layer applied by the leveling roller in this invention; Figure 9 This is a demonstration diagram of the fine sand polishing contact coating layer of the present invention; Figure 10 This is a top-view perspective structural diagram of the sand receiving box of the present invention; Figure 11 This is a three-dimensional structural diagram of the fine sand tube of the present invention; Figure 12 This is a three-dimensional structural diagram of the rotating shaft, spiral pushing blade, and sand pushing plate of the present invention; Figure 13 This is a demonstration diagram showing the fine sand falling from both ends of the sand-shaking diaphragm into the sand receiving box according to the present invention.

[0019] Explanation of the labels in the diagram: 101 Conveyor belt machine tool, 102 Sand bucket, 103 Electric slide rail, 104 Sliding bracket, 105 Compacting roller, 106 Leveling roller, 107 Rolling ruler, 108 Rolling gear, 2 Sand receiving box, 201 Fine sand pipe, 202 Peeling blade, 203 Sand outlet, 204 Sand shaking diaphragm, 205 High-speed electric slide table, 206 Rotary shaft, 207 Spiral pusher blade, 208 Sand pusher blade, 209 Fine sand bucket. Detailed Implementation

[0020] The technical solutions will now be clearly and completely described with reference to the accompanying drawings in the embodiments of the present invention.

[0021] The following implementation method: High-strength polypropylene nonwoven fabric, thickness: 0.9~2mm; polyethylene, model: MG70; thermoplastic polyolefin, model: TPOhifaxCA7320A; polyaryletherketone AV481, melt index: 55g / 10min (400℃, 2.16kg); polyaryletherketone AV651GF30BG20, melt index: 9g / 10min (400℃, 2.16kg); maleic anhydride grafted polyethylene, model: 41E755; The mixed rare earth elements, by oxide mass ratio, are: lanthanum oxide 10%, cerium oxide 17%, praseodymium oxide 9%, neodymium oxide 8%, holmium oxide 5%, erbium oxide 5%, ytterbium oxide 8%, scandium oxide 2%, samarium oxide 10%, yttrium oxide 12%, and gadolinium oxide 14%.

[0022] The primary raw materials for the first and second waterproof layers are polyethylene and rare earth elements, which can significantly improve the various performance indicators of the product. Adding nano-lanthanum oxide (La2O3) to the polyethylene waterproof layer can improve the material's thermal and oxygen stability, anti-aging, weather resistance, tensile strength, and elongation at break. Adding nano-cerium oxide (CeO2) to the polyethylene waterproof layer can improve the material's resistance to ultraviolet rays, oxidation, and aging, enhance thermal stability, and increase tensile strength and elongation at break. Adding nano-praseodymium oxide (Pr6O) to the polyethylene waterproof layer 11 It can improve the crystallinity of the product, and enhance tensile strength, high temperature resistance, weather resistance and anti-aging properties; Adding nano-neodymium oxide (Nd2O3) to the polyethylene waterproof layer can improve crystallinity, making the waterproof membrane denser, more impermeable, and enhancing tensile strength, puncture resistance, and dimensional stability. Adding nano-holmium oxide (Ho2O3) to the polyethylene waterproof layer can improve the product's low-temperature toughness, prevent cracking when bent at low temperatures, and enhance its UV resistance. Adding nano-erbium oxide (Er2O3) to a polyethylene waterproof layer can enhance its resistance to chemical corrosion (groundwater and saline-alkali), improve material uniformity, reduce the risk of pinholes, improve impermeability, and enhance surface gloss and density. Adding nano-ytterbium oxide (Yb2O3) to the polyethylene waterproof layer can refine the raw material grains, making the waterproof membrane denser and more impermeable, and significantly improving its puncture resistance and trampling resistance. Adding nano-scandium oxide (Sc2O3) to the polyethylene waterproof layer gives the product a strong toughening and strengthening effect, which can significantly enhance the material's impermeability and flexibility, and improve tensile strength. Adding nano samarium oxide (Sm2O3) to the polyethylene waterproof layer can improve the product's thermal and oxygen stability, inhibit high-temperature degradation, enhance low-temperature bending performance, and make it weather-resistant, acid and alkali-resistant, and less prone to decomposition when buried underground for a long time. Adding nano-yttrium oxide (Y2O3) to the polyethylene waterproof layer can improve the product's thermal stability, high temperature resistance, UV resistance, and anti-aging properties. Adding nano-gadolinium oxide (Gd2O3) to the polyethylene waterproof layer can improve the product's weather resistance and acid and alkali resistance, and effectively inhibit long-term degradation.

[0023] First implementation method: See attached document Figure 1 As shown, a method for preparing a double-layer pre-composite polymer pre-laid waterproof membrane includes the following steps: S1. Mix 50 parts of polyethylene, 30 parts of thermoplastic polyolefin, 10 parts of polyaryletherketone AV481, 15 parts of light calcium carbonate, 1 part of antioxidant, 2 parts of maleic anhydride grafted polyethylene, and 0.15 parts of mixed rare earth, and then extrude and mold to obtain a first waterproof layer sheet and a first waterproof layer sheet. The thickness of the first waterproof layer sheet and the first waterproof layer sheet is 0.8 mm. S2. Stack the first non-woven fabric, the first waterproof layer sheet, the second non-woven fabric, and the second waterproof layer sheet in sequence. Before the first non-woven fabric, the first waterproof layer, the second non-woven fabric, and the second waterproof layer enter the pressure roller, leave a 10cm section to be coated with adhesive at one end of the edge of the first non-woven fabric. After hot pressing, a double-layer composite polymer waterproof roll is obtained. S3. Apply hot melt adhesive to the second waterproof layer sheet of the double-layer composite polymer waterproof membrane to form an adhesive layer. Then, cover the other end of the edge of the second waterproof layer sheet (in the opposite direction to the reserved end of the first non-woven fabric edge) with an edge film with a width of 10cm. S4. The composite polymer waterproof membrane with the adhesive layer applied and the edges wrapped and covered is fed into the sand planting equipment to form a sand coating layer on the outer surface of the adhesive layer. After cooling, a double-layer pre-composite polymer pre-laid waterproof membrane is obtained. S5. Apply hot melt adhesive to the edge of the first waterproof layer of the double-layer pre-composite polymer pre-laid waterproof membrane to form an overlapping edge adhesive layer, and then apply the edge film.

[0024] Second implementation method: S1. Mix 55 parts of polyethylene, 35 parts of thermoplastic polyolefin, 12 parts of polyaryletherketone AV481, 18 parts of kaolin, 1 part of antioxidant 1010, 2 parts of maleic anhydride grafted polyethylene, and 0.17 parts of mixed rare earth, and then extrude and mold to obtain a first waterproof layer sheet and a second waterproof layer sheet. The thickness of both the first waterproof layer sheet and the second waterproof layer sheet is 0.9 mm. S2. Stack the first non-woven fabric, the first waterproof layer sheet, the second non-woven fabric, and the second waterproof layer sheet in sequence. Before the first non-woven fabric, the first waterproof layer, the second non-woven fabric, and the second waterproof layer enter the pressure roller, leave a 10cm section to be coated with adhesive at one end of the edge of the first non-woven fabric. After hot pressing, a double-layer composite polymer waterproof roll is obtained. S3. Apply hot melt adhesive to the second waterproof layer sheet of the double-layer composite polymer waterproof membrane to form an adhesive layer. Then, cover the other end of the edge of the second waterproof layer sheet (in the opposite direction to the reserved end of the first non-woven fabric edge) with an edge film with a width of 10cm. S4. The composite polymer waterproof membrane with the adhesive layer applied and the edges wrapped and covered is fed into the sand planting equipment to form a sand coating layer on the outer surface of the adhesive layer. After cooling, a double-layer pre-composite polymer pre-laid waterproof membrane is obtained. S5. Apply hot melt adhesive to the edge of the first waterproof layer of the double-layer pre-composite polymer pre-laid waterproof membrane to form an overlapping edge adhesive layer, and then apply the edge film.

[0025] The third implementation method: S1. Mix 60 parts of polyethylene, 40 parts of thermoplastic polyolefin, 15 parts of polyaryletherketone AV481, 20 parts of talc, 2 parts of antioxidant 168, 3 parts of maleic anhydride grafted polyethylene, and 0.18 parts of mixed rare earth, and then extrude and mold to obtain a first waterproof layer sheet and a second waterproof layer sheet. The thickness of both the first waterproof layer sheet and the second waterproof layer sheet is 1 mm. S2. Stack the first non-woven fabric, the first waterproof layer sheet, the second non-woven fabric, and the second waterproof layer sheet in sequence. Before the first non-woven fabric, the first waterproof layer, the second non-woven fabric, and the second waterproof layer enter the pressure roller, leave a 10cm section to be coated with adhesive at one end of the edge of the first non-woven fabric. After hot pressing, a double-layer composite polymer waterproof roll is obtained. S3. Apply hot melt adhesive to the second waterproof layer sheet of the double-layer composite polymer waterproof membrane to form an adhesive layer. Then, cover the other end of the edge of the second waterproof layer sheet (in the opposite direction to the reserved end of the first non-woven fabric edge) with an edge film with a width of 10cm. S4. The composite polymer waterproof membrane with the adhesive layer applied and the edges wrapped and covered is fed into the sand planting equipment to form a sand coating layer on the outer surface of the adhesive layer. After cooling, a double-layer pre-composite polymer pre-laid waterproof membrane is obtained. S5. Apply hot melt adhesive to the edge of the first waterproof layer of the double-layer pre-composite polymer pre-laid waterproof membrane to form an overlapping edge adhesive layer, and then apply the edge film.

[0026] Fourth implementation method: The only difference between this embodiment and the first embodiment is that the mixed rare earth elements are in the following oxide mass ratio: lanthanum oxide 12%, cerium oxide 15%, praseodymium oxide 9%, neodymium oxide 8%, holmium oxide 5%, erbium oxide 5%, ytterbium oxide 8%, scandium oxide 2%, samarium oxide 10%, yttrium oxide 12%, and gadolinium oxide 14%.

[0027] Fifth implementation method: The only difference between this embodiment and the second embodiment is that the mixed rare earth elements are in the following oxide mass ratio: lanthanum oxide 12%, cerium oxide 15%, praseodymium oxide 9%, neodymium oxide 8%, holmium oxide 5%, erbium oxide 5%, ytterbium oxide 8%, scandium oxide 2%, samarium oxide 10%, yttrium oxide 12%, and gadolinium oxide 14%.

[0028] Sixth implementation method: The only difference between this embodiment and the third embodiment is that the mixed rare earth elements are in the following oxide mass ratio: lanthanum oxide 12%, cerium oxide 15%, praseodymium oxide 9%, neodymium oxide 8%, holmium oxide 5%, erbium oxide 5%, ytterbium oxide 8%, scandium oxide 2%, samarium oxide 10%, yttrium oxide 12%, and gadolinium oxide 14%.

[0029] Seventh implementation method: The only difference between this embodiment and the first embodiment is that the mixed rare earth elements are in the following oxide mass ratio: lanthanum oxide 14%, cerium oxide 13%, praseodymium oxide 9%, neodymium oxide 8%, holmium oxide 5%, erbium oxide 5%, ytterbium oxide 8%, scandium oxide 2%, samarium oxide 10%, yttrium oxide 12%, and gadolinium oxide 14%.

[0030] Eighth implementation method: The only difference between this embodiment and the second embodiment is that the mixed rare earth elements are in the following oxide mass ratio: lanthanum oxide 14%, cerium oxide 13%, praseodymium oxide 9%, neodymium oxide 8%, holmium oxide 5%, erbium oxide 5%, ytterbium oxide 8%, scandium oxide 2%, samarium oxide 10%, yttrium oxide 12%, and gadolinium oxide 14%.

[0031] Ninth implementation method: The only difference between this embodiment and the third embodiment is that the mixed rare earth elements are in the following oxide mass ratio: lanthanum oxide 14%, cerium oxide 13%, praseodymium oxide 9%, neodymium oxide 8%, holmium oxide 5%, erbium oxide 5%, ytterbium oxide 8%, scandium oxide 2%, samarium oxide 10%, yttrium oxide 12%, and gadolinium oxide 14%.

[0032] Comparative implementation methods: The only difference between this comparative embodiment and the first embodiment is that no mixed rare earth elements are added.

[0033] The double-layer pre-composite polymer pre-laid waterproof membranes prepared according to the first to ninth embodiments and the comparative embodiment were subjected to tensile tests according to the methods in GB / T328.9-2007 "Test Methods for Building Waterproofing Membranes Part 9: Tensile Properties of Polymer Waterproofing Membranes". The test results are shown in the table below:

[0034] Compared with the comparative embodiment, the first embodiment adds mixed rare earth elements to the waterproof layer. As a result, the tensile strength of the double-layer pre-composite polymer pre-laid waterproof membrane prepared by the first embodiment is higher than that of the comparative embodiment, indicating that adding mixed rare earth elements to the waterproof layer can improve the mechanical strength of the double-layer pre-composite polymer pre-laid waterproof membrane.

[0035] Compared with the comparative embodiments, the fourth to ninth embodiments changed the composition percentage of lanthanum oxide and cerium oxide in the mixed rare earth. As a result, the tensile strength of the double-layer pre-composite polymer pre-laid waterproof membrane prepared in the fourth to ninth embodiments was higher than that in the first and third embodiments. This shows that changing the percentage composition of lanthanum oxide and cerium oxide in the mixed rare earth can further improve the tensile strength of the double-layer pre-composite polymer pre-laid waterproof membrane. Among them, the double-layer pre-composite polymer pre-laid waterproof membrane prepared in the fifth embodiment has a higher tensile strength.

[0036] The double-layer pre-composite polymer pre-laid waterproof membranes prepared in the first to ninth embodiments and the comparative embodiment were immersed in a 5% sodium hydroxide solution for 168 hours, and their tensile strength retention rate was tested; they were also immersed in a 5% sodium sulfate and dilute sulfuric acid mixture for 168 hours, and their tensile strength retention rate was tested; tensile strength retention rate = tensile strength after immersion / tensile strength before immersion × 100%; the test results are shown in the table below:

[0037] Compared with the comparative embodiment, the first embodiment adds mixed rare earth elements to the waterproof layer. As a result, the tensile strength retention rate of the double-layer pre-composite polymer pre-laid waterproof membrane prepared by the first embodiment is higher than that of the comparative embodiment, indicating that adding mixed rare earth elements to the waterproof layer can improve the corrosion resistance of the double-layer pre-composite polymer pre-laid waterproof membrane.

[0038] Compared with the comparative embodiments, the fourth to ninth embodiments changed the composition percentage of lanthanum oxide and cerium oxide in the mixed rare earth. As a result, the corrosion resistance of the double-layer pre-composite polymer pre-laid waterproof membrane prepared in the fourth to ninth embodiments was higher than that in the first and second embodiments. This shows that changing the composition percentage of lanthanum oxide and cerium oxide in the mixed rare earth can further improve the corrosion resistance of the double-layer pre-composite polymer pre-laid waterproof membrane. Among them, the double-layer pre-composite polymer pre-laid waterproof membrane prepared in the seventh embodiment has higher acid corrosion resistance, and the double-layer pre-composite polymer pre-laid waterproof membrane prepared in the fifth embodiment has higher alkali corrosion resistance.

[0039] The double-layer pre-composite polymer pre-laid waterproof membranes prepared according to the first to ninth embodiments and the comparative embodiment were subjected to low-temperature resistance tests according to GB / T328.15-2007 "Test Methods for Building Waterproof Membranes Part 15: Low-Temperature Bending of Polymer Waterproof Membranes". The test results are shown in the table below:

[0040] Compared with the comparative embodiment, the first embodiment adds mixed rare earth elements to the waterproof layer. As a result, the low-temperature resistance of the double-layer pre-composite polymer pre-laid waterproof membrane prepared by the first embodiment is higher than that of the comparative embodiment, indicating that adding mixed rare earth elements to the waterproof layer can improve the low-temperature resistance of the double-layer pre-composite polymer pre-laid waterproof membrane.

[0041] Compared with the comparative embodiments, the fourth to ninth embodiments changed the composition percentage of lanthanum oxide and cerium oxide in the mixed rare earth. As a result, the low-temperature resistance of the double-layer pre-composite polymer pre-laid waterproof membrane prepared in the fifth to ninth embodiments was higher than that in the first to third embodiments. This shows that changing the composition percentage of lanthanum oxide and cerium oxide in the mixed rare earth can further improve the corrosion resistance of the double-layer pre-composite polymer pre-laid waterproof membrane. Among them, the double-layer pre-composite polymer pre-laid waterproof membrane prepared in the fifth and eighth embodiments has higher low-temperature resistance.

[0042] The tenth implementation method: See attached document Figures 2 to 9As shown, the sand-planting equipment includes a conveyor belt machine 101 for transporting double-layer composite polymer waterproof membrane and a sand bucket 102 for uniformly dropping sand. The sand bucket 102 is fixed above the starting end of the conveyor belt machine 101. The double-layer composite polymer waterproof membrane with an adhesive coating is placed on the conveyor belt machine 101 for transport. The coarse sand falling from the sand bucket 102 is spread evenly on the surface of the adhesive coating. Electric slide rails 103 are fixedly connected to both ends of the conveyor belt machine 101. The movable ends of the two electric slide rails 103 are fixedly connected to sliding brackets 104 in the same direction as the transmission movement of the conveyor belt machine 101. A compaction roller 105 and a leveling roller 106 are rotatably connected between the top and bottom of the conveyor belt machine tool 101. Rolling rulers 107 are fixedly connected to the top and bottom edges of both ends of the conveyor belt machine tool 101. Rolling gears 108 are fixedly connected to both ends of the compaction roller 105 and the leveling roller 106. The rolling rulers 107 mesh with the rolling gears 108. The sliding bracket 104 is driven by the electric slide rail 103, which drives the compaction roller 105 and the leveling roller 106 to move back and forth repeatedly. The meshing of the rolling gears 108 and the rolling rulers 107 effectively improves the rolling stability of the compaction roller 105 and the leveling roller 106. The coarse sand falling from the sand hopper 102 is spread evenly on the surface of the adhesive layer (the coarse sand particles are 40 mesh). The compaction roller 105 compacts the coarse sand layer spread on the double-layer composite polymer waterproof membrane, so that the gravel at the bottom of the coarse sand layer is fully embedded in the adhesive layer, which effectively improves the bonding effect between the sand coating layer and the adhesive layer. In addition, the coarse sand layer effectively blocks the compaction roller 105 from the adhesive layer, thereby effectively preventing the adhesive layer from sticking to the compaction roller 105.

[0043] A sand receiving box 2 is placed at the bottom of the other end of the conveyor belt machine tool 101. A fine sand pipe 201 is fixedly connected to the top of the sand receiving box 2. A peeling plate 202 is fixedly connected to the top of the fine sand pipe 201 away from the sand hopper 102. The top of the peeling plate 202 slides in contact with the double-layer composite polymer waterproof membrane being transported below the conveyor belt machine tool 101. As the conveyor belt machine tool 101 continues to move the double-layer composite polymer waterproof membrane, the coarse sand layer laid flat on the double-layer composite polymer waterproof membrane is overturned when the conveyor belt machine tool 101 flips downward and reverses. This causes the gravel that is not in contact with the adhesive layer to fall into the sand receiving box 2. Then, the peeling blade 202 scrapes off the gravel that is not in close contact with the adhesive layer, while retaining the gravel that is in close contact. Subsequently, the leveling roller 106 applies pressure to the double-layer composite polymer waterproof membrane to further compact the gravel protruding from the surface of the adhesive layer, thereby shaping the sand surface of the sand layer and ensuring that the sand surface of the sand layer maintains a consistent flatness, thus effectively improving the forming quality of the sand layer.

[0044] Eleventh implementation method: Compared to the first embodiment, the main addition is a sand-shaking film 204, the specific addition structure is as follows, and the rest of the structure is the same as the first embodiment.

[0045] See attached document Figure 8 , Figure 9 and Figure 10 As shown, the sand receiving box 2 is divided into a coarse sand receiving area and a fine sand receiving area. The coarse sand receiving area is located near the end of the conveyor belt machine tool 101 away from the sand hopper 102, which facilitates the receiving of the coarse sand falling into the coarse sand receiving area. The coarse sand receiving area and the fine sand receiving area are symmetrically distributed about the fine sand pipe 201. The top of the fine sand pipe 201 is provided with a sand outlet 203 at the end near the fine sand receiving area. A sand shaking diaphragm 204 is fixedly connected to the outside of the sand outlet 203. Both ends of the bottom of the fine sand pipe 201 are fixedly connected to a high-speed electric slide table 205 (the high-speed electric slide table 205 is a linear motion unit integrating a servo / stepper motor, transmission mechanism, linear guide rail, aluminum profile base, dust protection, and limit sensor. Its core requirements are high speed, high acceleration, and high frequency reciprocating). The end of the sand shaking diaphragm 204 away from the sand outlet 203 is fixedly connected to the movable end of the high-speed electric slide table 205. Before the leveling roller 106 applies pressure to the double-layer composite polymer waterproof membrane, fine sand (80 mesh) from the fine sand pipe 201 is conveyed to the sand-shaking membrane 204 through the sand outlet 203. The high-speed electric slide 205 drives the sand-shaking membrane 204 to repeatedly retract and expand. See attached diagram for details. Figure 9 As shown, the fine sand on the sand-shaking film 204 is thrown upwards, so that the fine sand comes into contact with and adheres to the coating layer. The fine sand fills the gaps between the coarse sand, effectively reducing the exposed area of ​​the coating layer. Subsequently, when it comes into contact with the leveling roller 106, it effectively reduces the possibility of the coating layer sticking to the leveling roller 106, and effectively improves the smoothness of the sand surface of the coating layer.

[0046] See attached document Figure 11 , Figure 12 and Figure 13 As shown, a rotating shaft 206 is rotatably connected inside the fine sand pipe 201. Spiral pusher blades 207 and sand pusher plates 208 are alternately fixedly connected to the outside of the rotating shaft 206. The sand pusher plates 208 are arranged parallel to the axial direction of the rotating shaft 206, and the edge of the sand pusher plates 208 slides in contact with the inner wall of the fine sand pipe 201. Fine sand hoppers 209 are fixedly connected to both ends of the fine sand pipe 201. Fine sand can be conveniently fed into the fine sand pipe 201 from both ends using the fine sand hoppers 209. Multiple spiral pusher blades 207 are symmetrically arranged about the middle of the rotating shaft 206. As the rotating shaft 206 rotates, the spiral pusher blades 207 on the rotating shaft 206 spirally push the fine sand at both ends of the fine sand tube 201 towards the middle of the fine sand tube 201. Simultaneously, the sand pusher blades 208 on the rotating shaft 206 push the fine sand upwards along the inner wall of the fine sand tube 201 and push the fine sand outwards from the sand outlet 203. The pushed-out fine sand falls onto the shaking diaphragm 204, where it is evenly distributed as the shaking diaphragm 204 vibrates. Specifically, when the shaking diaphragm 204 retracts, as... Figure 13 As shown, the middle part of the sand-shaking diaphragm 204 is V-shaped, so that the fine sand is evenly spread in a line. During the spreading process, the excess fine sand on the sand-shaking diaphragm 204 falls directly from both ends of the sand-shaking diaphragm 204 into the fine sand receiving area of ​​the sand receiving box 2, which facilitates the recycling of fine sand.

[0047] The above description is merely a preferred embodiment of the present invention; it encompasses all the protection scope of the present invention. Any equivalent substitutions or modifications made by those skilled in the art within the technical scope disclosed in the present invention, based on the technical solutions and improved concepts of the present invention, should be covered within the protection scope of the present invention.

Claims

1. A double-layer pre-composite polymer pre-laid waterproof membrane, characterized in that, From bottom to top, it includes a first nonwoven fabric, a first waterproof layer, a second nonwoven fabric, a second waterproof layer, an adhesive layer, and a sand coating layer. One edge of the first waterproof layer and the other edge of the second waterproof layer are provided with an overlapping adhesive layer. The first waterproof layer and the second waterproof layer each independently include the following raw materials in parts by weight: 50-60 parts of polyethylene, 30-40 parts of thermoplastic polyolefin, 10-15 parts of polyaryletherketone, 15-20 parts of filler, 1-2 parts of antioxidant, 2-3 parts of compatibilizer, and 0.15-0.18 parts of mixed rare earth elements. The adhesive coating and the overlapping edge adhesive layer are both hot melt adhesives and butyl adhesives; The sand coating layer includes one or more of the following: alumina ceramics, sintered kaolin ceramsite, sintered quartz sand, and sintered refractory clay aggregate.

2. The double-layer pre-composite polymer pre-laid waterproof membrane according to claim 1, characterized in that: The polyaryletherketone is composed of a first polyaryletherketone and a second polyaryletherketone, the first polyaryletherketone and the second polyaryletherketone have different melt indices, the melt index of the first polyaryletherketone is 55 g / 10 min and the melt index of the second polyaryletherketone is 9 g / 10 min, and the mass ratio of the first polyaryletherketone to the second polyaryletherketone is 1 to 3:

5.

3. The double-layer pre-composite polymer pre-laid waterproof membrane according to claim 1, characterized in that: Both the first and second nonwoven fabrics are high-strength polypropylene nonwoven fabrics, and the cutting width of the first nonwoven fabric is reduced by 10cm compared to the cutting width of the first waterproof layer.

4. The double-layer pre-composite polymer pre-laid waterproof membrane according to claim 1, characterized in that: The filler includes one or more of light calcium carbonate, kaolin, and talc, and the compatibilizer is maleic anhydride-grafted polyethylene.

5. The double-layer pre-composite polymer pre-laid waterproof membrane according to claim 1, characterized in that: The mixed rare earth elements are in the following oxide mass ratios: lanthanum oxide 10-14%, cerium oxide 13-17%, praseodymium oxide 7-11%, neodymium oxide 6-10%, holmium oxide 3-7%, erbium oxide 3-7%, ytterbium oxide 6-10%, scandium oxide 1-3%, samarium oxide 8-12%, yttrium oxide 10-14%, and gadolinium oxide 12-16%.

6. The preparation method of the double-layer pre-composite polymer pre-laid waterproof membrane according to claim 1, characterized in that, Includes the following steps: S1. The raw materials of the first waterproof layer and the second waterproof layer are mixed separately, and then extruded and molded to obtain the first waterproof layer sheet and the second waterproof layer sheet; S2. The layers are stacked in the order of first non-woven fabric, first waterproof layer, second non-woven fabric, and second waterproof layer from bottom to top. A 10cm section to be coated with adhesive is reserved at one end of the edge of the first non-woven fabric. After hot pressing, a double-layer composite polymer waterproof membrane is obtained. S3. Apply hot melt adhesive to the second waterproof layer of the double-layer composite polymer waterproof membrane to form an adhesive layer. Then, cover the other end of the edge of the second waterproof layer (in the opposite direction to the reserved end of the first non-woven fabric edge) with a 10cm wide edge film. S4. The composite polymer waterproof membrane with the adhesive layer and edge film is fed into the sand planting equipment to form a sand coating layer on the outer surface of the adhesive layer. After cooling, a double-layer pre-composite polymer pre-laid waterproof membrane is obtained. S5. Apply hot melt adhesive to the edge of the first waterproof layer of the double-layer pre-composite polymer pre-laid waterproof membrane to form an overlapping edge adhesive layer, and then cover with edge film.

7. The preparation method of the double-layer pre-composite polymer pre-laid waterproof membrane according to claim 6, characterized in that: The sand planting equipment used in step S3 includes a conveyor belt machine (101) for conveying double-layer composite polymer waterproof membrane and a sand bucket (102) for making the sand fall evenly. The sand bucket (102) is fixed above the starting end of the conveyor belt machine (101). Electric slide rails (103) are fixedly connected to both the left and right ends of the conveyor belt machine (101). The movable ends of the two electric slide rails (103) are fixedly connected to sliding brackets (104) in the same direction as the transmission movement of the conveyor belt machine (101). Compacting rollers (105) and leveling rollers (106) are rotatably connected between the top and bottom of the two sliding brackets (104). The compaction roller (105) is used for the double-layer composite polymer waterproof membrane conveyed above the roller pressing conveyor belt machine (101), and the leveling roller (106) is used for the double-layer composite polymer waterproof membrane conveyed below the roller pressing conveyor belt machine (101). A sand receiving box (2) is placed at the bottom of the other end of the conveyor belt machine tool (101). A fine sand pipe (201) is fixedly connected to the top of the sand receiving box (2). A peeling plate (202) is fixedly connected to the top of the fine sand pipe (201) away from the sand hopper (102). The top of the peeling plate (202) slides in contact with the double-layer composite polymer waterproof membrane being transported below the conveyor belt machine tool (101).

8. The preparation method of the double-layer pre-composite polymer pre-laid waterproof membrane according to claim 7, characterized in that: Rolling rulers (107) are fixedly connected to the top and bottom edges of both ends of the conveyor belt machine tool (101). Rolling gears (108) are fixedly connected to both ends of the compaction roller (105) and the leveling roller (106). The rolling rulers (107) mesh with the rolling gears (108).

9. The preparation method of the double-layer pre-composite polymer pre-laid waterproof membrane according to claim 7, characterized in that: The sand receiving box (2) is divided into a coarse sand receiving area and a fine sand receiving area. The coarse sand receiving area is located near the end of the conveyor belt machine tool (101) away from the sand hopper (102). The coarse sand receiving area and the fine sand receiving area are symmetrically distributed about the fine sand pipe (201). The top of the fine sand pipe (201) is provided with a sand outlet (203) near the fine sand receiving area. A sand shaking diaphragm (204) is fixedly connected to the outside of the sand outlet (203). Both ends of the bottom of the fine sand pipe (201) are fixedly connected to a high-speed electric slide (205). The end of the sand shaking diaphragm (204) away from the sand outlet (203) is fixedly connected to the movable end of the high-speed electric slide (205).

10. The preparation method of the double-layer pre-composite polymer pre-laid waterproof membrane according to claim 9, characterized in that: The fine sand pipe (201) is rotatably connected to a rotating shaft (206). The rotating shaft (206) is alternately fixedly connected to a spiral pusher blade (207) and a sand pusher (208) in sequence. The sand pusher (208) is arranged parallel to the axial direction of the rotating shaft (206), and the edge of the sand pusher (208) slides in contact with the inner wall of the fine sand pipe (201). Both ends of the fine sand pipe (201) are fixedly connected to fine sand hoppers (209). The multiple spiral pusher blades (207) are symmetrically arranged about the middle of the rotating shaft (206).

Citation Information

Patent Citations

  • Preparation process of weather-resistant modified asphalt waterproof coiled material added with rare earth elements

    CN117924956A